2020
DOI: 10.1177/1060028020938059
|View full text |Cite
|
Sign up to set email alerts
|

Ertapenem Neurotoxicity in Hemodialysis Patients—Safe and Effective Dosing Is Still Needed: A Retrospective Study and Literature Review

Abstract: Background: The approved dosing of ertapenem in patients with chronic kidney disease stage 5 utilizing dialysis (CKD-5D) is 0.5 g intravenous daily. Several reports associated this dosing strategy with neurotoxicity. Objective: The purpose of this study is to identify the incidence of neurotoxicity in this population and the risk factors associated with this toxicity. The secondary objective was to review the literature and discuss a safer/cost-effective dosing strategy based on available data. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
(87 reference statements)
2
14
0
Order By: Relevance
“…In a study on the AUC0-∞ of 1 g daily ertapenem in CKD 5D patients, it was found that the free drug concentration was five folds higher than in patients with mild renal impairment at eGFR > 30 [ 2 ]. This could be excessive as identified in our case and several other case reports [ 1 , 10 ]. A recent pharmacokinetic study of the effects of ertapenem when administered as a 500 mg dose three times weekly found that a plasma concentration above 2 mg/L was maintained (selected based on the MIC90 and the CLSI/FDA susceptibility breakpoint) [ 11 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In a study on the AUC0-∞ of 1 g daily ertapenem in CKD 5D patients, it was found that the free drug concentration was five folds higher than in patients with mild renal impairment at eGFR > 30 [ 2 ]. This could be excessive as identified in our case and several other case reports [ 1 , 10 ]. A recent pharmacokinetic study of the effects of ertapenem when administered as a 500 mg dose three times weekly found that a plasma concentration above 2 mg/L was maintained (selected based on the MIC90 and the CLSI/FDA susceptibility breakpoint) [ 11 ].…”
Section: Discussionsupporting
confidence: 66%
“…This difference in the onset of symptoms may be due to lack of awareness of the symptoms, and other contributing factors in our patient such as older age, low albumin and morbid obesity. In a retrospective study of ertapenem-induced seizures among CKD 5D patients, male sex, dementia and concomitant use of antibiotics were found to be the main predictors of seizure [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al measured blood ertapenem levels and demonstrated that even this dose can cause toxicity in routine hemodialysis patients, despite the fact that up to 70% is eliminated by hemodialysis (4). Again, in the study of El Nekidy et al, it was emphasized that the neurotoxic effects could continue in CKD-5D patients at a dose of 500 mg/day and it was stated that alternative dosage or administration strategies should be developed (8). Central nervous system toxicity with ertapenem use generally occurs in the geriatric population.…”
Section: Discussionmentioning
confidence: 99%